HOMEROOM TEACHING OF PHYSICAL EDUCATION AND ITS CONTRIBUTION TO PUPILS’ PHYSICAL ACTIVITY - Sinđelić, Nenad M. (Metodička teorija i praksa, 2024)
The aim of this paper is to review the place and significance of physical education (PE) classes in the younger grades of primary school, both within the physical education system and the educational system in general. The contribution of such organized teaching to pupils’ physical activities and the possibility for them to be physically active on a daily basis will be pointed out. Additionally, the intention of this paper is to emphasize the necessity of regular physical activity, particularly at the younger school age, and the numerous positive effects that that participation in these activities produce for the body. The World Health Organization recommends 60 minutes of moderate to intense physical activity every day. Unfortunately, data indicate that a significant percentage of children and adolescents fail to meet even the recommended minimum, with physical activity levels showing a tendency to decline with age, and sedentary lifestyles being prevalent among this population. Insufficient physical activity can also result in negative impacts on health status. Given its purpose and broad reach, the school is one of the key points for implementing certain interventions in order to overcome these problems. The teacher’s daily interaction with pupils during school hours inevitably aids in understanding their personalities, enabling the structuring of relevant and engaging content that would provide incentives for regular physical activity of various types and levels. This is precisely where the “power” of homeroom teaching of PE lies, as the content of physical activities can be applied throughout the entire school environment, not solely confined to PE classes. With ongoing monitoring of pupils’ progress throughout the whole teaching process, there is an opportunity for faster identification of children at an increased risk of engaging in sedentary activities, allowing for targeted interventions to be implemented.
Keywords: physical activities; physical education (PE); homeroom teaching; pupil